Multiple GPCR Functional Assays Based on Resonance Energy Transfer Sensors - Zhou, Yiwei; Meng, Jiyong; Xu, Chanjuan; Liu, Jianfeng (Frontiers in Cell and Developmental Biology, 2021)
G protein-coupled receptors (GPCRs) represent one of the largest membrane protein families that participate in various physiological and pathological activities. Accumulating structural evidences have revealed how GPCR activation induces conformational changes to accommodate the downstream G protein or β-arrestin. Multiple GPCR functional assays have been developed based on Förster resonance energy transfer (FRET) and bioluminescence resonance energy transfer (BRET) sensors to monitor the conformational changes in GPCRs, GPCR/G proteins, or GPCR/β-arrestin, especially over the past two decades. Here, we will summarize how these sensors have been optimized to increase the sensitivity and compatibility for application in different GPCR classes using various labeling strategies, meanwhile provide multiple solutions in functional assays for high-throughput drug screening.